2012
DOI: 10.3390/md10051044
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation, Biotransformation, Histopathology and Paralysis in the Pacific Calico Scallop Argopecten ventricosus by the Paralyzing Toxins of the Dinoflagellate Gymnodinium catenatum

Abstract: The dinoflagellate Gymnodinium catenatum produces paralyzing shellfish poisons that are consumed and accumulated by bivalves. We performed short-term feeding experiments to examine ingestion, accumulation, biotransformation, histopathology, and paralysis in the juvenile Pacific calico scallop Argopecten ventricosus that consume this dinoflagellate. Depletion of algal cells was measured in closed systems. Histopathological preparations were microscopically analyzed. Paralysis was observed and the time of recove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 79 publications
1
10
1
Order By: Relevance
“…So, an increase in clapping time, as observed here, might result from the response of the smooth adductor muscle to bioactive compounds, as suggested by the haemocyte infiltrations into the muscle of BEC-exposed scallops. Such haemocyte infiltrations in the adductor muscle have previously been observed in A. ventricosus exposed to Gymnodinium catenatum (Escobedo-Lozano et al 2012), and this has been interpreted as a defence mechanism to evacuate bioactive extracellular compounds and limit the alteration of the muscle.…”
Section: Escape Behavioursupporting
confidence: 54%
See 1 more Smart Citation
“…So, an increase in clapping time, as observed here, might result from the response of the smooth adductor muscle to bioactive compounds, as suggested by the haemocyte infiltrations into the muscle of BEC-exposed scallops. Such haemocyte infiltrations in the adductor muscle have previously been observed in A. ventricosus exposed to Gymnodinium catenatum (Escobedo-Lozano et al 2012), and this has been interpreted as a defence mechanism to evacuate bioactive extracellular compounds and limit the alteration of the muscle.…”
Section: Escape Behavioursupporting
confidence: 54%
“…Bricelj et al (2005) showed that burrowing of Mya arenaria was not affected by exposure to non-PST-producing A. tamarense strain (CCMP115), but that incapacity to burrow was toxin-induced in clams and resulted from muscle paralysis (Bricelj et al, 1990;. The link between the accumulation of PSTs and the paralysis of the adductor muscle has been observed in several bivalve species, such as C. gigas, M. edulis or A. ventricosus exposed to PST-producing dinoflagellates (Hégaret et al, 2007;Galimany et al, 2008;Escobedo-Lozano et al, 2012). Moreover, the injection of gonyautoxin (GTX, a saxitoxinlike toxin), produced by G. catenatum, into the muscle of the scallop N. subnodosus induced paralysis (Estrada et al, 2010).…”
Section: Behavioral and Physiological Effects Associated To Exposure mentioning
confidence: 99%
“…Examination under an optical microscope of the cell debris, after homogenization, showed that the cells were completely disrupted. The starting material was a largescale laboratory culture of G. catenatum, and its principal toxin was N-sulfo-carbamoyl (C1, C2), as previously described (Estrada et al, 2007;Escobedo-Lozano et al, 2012). As described by Laycock et al (1994), these N-sulfo-carbamoyl toxins were extracted and chemically converted to their analog carbamates, a mixture of GTX 2/3 (∼3:1).…”
Section: Extraction Identification and Quantification Of Toxinsmentioning
confidence: 99%
“…catenella (ACDH strain) [ 38 , 48 ]. Briefly, 2-year-old adult scallops were collected and acclimated in filtered and aerated seawater at 12–13 °C for three weeks for depuration by feeding the non-toxic algae, Isochrysis galbana (7.5 × 10 5 cells/mL) as the control group [ 59 ]. 18 scallops were separated into independent tanks with aeration, and 6 groups with 3 individuals for each were taken at different test time points (0, 1, 3, 5, 10, and 15 days) during the challenging experiments.…”
Section: Methodsmentioning
confidence: 99%